Structure formations and properties of natural anhydrite at complex activation - A. F. Gordina; I. S. Polyanskikh; A. N. Gumeniuk; T. A. Plekhanova (Vestnik MGSU)
Introduction. The subject of the research is the improvement of physical and mechanical characteristics of binder based on natural anhydrite from the Ergachevskoye deposit. The application of natural anhydrite will provide the production of construction materials on the basis of nonfired, low-energy-cost binders. Complex activation of hardening is offered for improvement of physical and mechanical characteristics. The compositions from quantity and content of chemical activator are optimized. The use of metallurgical dust as an additional component of the complex additive, providing improvement of hydrophysical properties is proposed.Materials and methods. For the production of binder natural anhydrite stone was crushed in a jaw crusher and ground in a laboratory disc mill. Determination of strength parameters and establishment of the optimum activator were carried out using a hydraulic laboratory press. The chemical composition of metallurgical dust was analyzed using X-ray fluorescent spectrometer with wave dispersion. The nature of structure formation and the presence of neoplasms were determined using scanning electron microscopes and a differential-scanning calorimeter.Results. A comparative analysis of the influence of hardening activators on the strength characteristics of natural anhydrite-based binder was carried out. Activation by iron sulfate (melanterite) and sodium hydrosulfite; sodium and potassium hydroxide; air-setting lime and cement was analyzed. However, the complex effect of modifiers is achieved only with the combination of chemical and mineral hardening activators and provides not only an increase in strength characteristics, but also water resistance.Conclusions. Complex activation of natural anhydrite hardening provides the formation of a matrix with increased density. The matrix is composed of gypsum crystalline hydrates of optimal morphology, additionally bonded by amorphous new formations based on hydrosilicates, hydrosulfoaluminosilicates or calcium hydroferrites. Such a structure provides physical and mechanical characteristics at a level sufficient for the production of wall building blocks.